Coloured Cognitive Maps for Modelling Decision Contexts - Venable, John (ceur-ws.org, 2005)
Cognitive Mapping is a form of Causal Mapping developed and popularised by Colin Eden and Fran Ackermann (Eden, 1988, Eden & Ackermann, 2001, Ackermann and Eden, 2001). This paper reports on research in progress to develop, test, and employ extensions to cognitive mapping to support decision making in the context of problem formulation and solutions derivation, comparison, and choice. The paper describes extensions to the method and notation, include the use of colour (or bolding) to indicate whether nodes are desirable or undesirable, the conception of two forms of cognitive maps, the first of which focuses on the current, undesirable context and the second on a desired, future context (and how to achieve it), and a procedure for developing and converting between these two forms of cognitive maps. The paper also describes the current state of the research on coloured cognitive maps, open issues, and planned and proposed future research.